Methodology for Rationalising the Distribution of Limited Material Resources Considering the Importance and Initial Adequate Supply of Facilities - Volodymyr Herasymenko; Julia Lutsyk; Pavlo Parhomenko; Olexander Demenev; Volodymyr Mirnenko (Науковий вісник Мукачівського державного університету. Серія Економіка, 2021)
The organisation of resource support for the needs of the Armed Forces of Ukraine is an important daily task related to the distribution of material resources for their intended purpose. If there is a sufficient resource base and the factors of time, speed, and priority of delivery of funds are secondary, resource support is carried out according to the principles “if necessary” and “if possible”. However, the practices of resource support for the needs of the Armed Forces of Ukraine considering the limited resource capabilities of the national economy and other similar tasks, as a rule, demonstrates the necessity of acting in the conditions of quantitative and qualitative restrictions of the resource base. Moreover, in the conditions of requirements for reducing the time of implementation of resource support, considering the priority of resource assignment objects and different levels of their initial resource provision. The purpose of this study is to find the best, rational, and even optimal distribution of resources for certain characteristics in three types of business conditions: certainty, uncertainty, and risk in managerial decision-making. Based on the analysis of available methods of nonlinear programming in distribution problems, proceeding from the condition of maintaining mathematical correctness and accessibility to practical use, the study presents the procedure for applying the maximum element method. The proposed approach to optimising the distribution problem is considered on the example of possible distribution options for equally efficient resource supply between the resource supply facilities. The options differ in the values of the importance of objects and the levels of initial supply in relative units at the time of decision-making on the allocation of resources upon providing resources for a certain final management task. The methodology of this study can be used in planning and decision-making related to the distribution of resources in organisational systems of military and civil administration, considering the importance and initial state of adequate supply of destination facilities in case of limited capabilities of the resource manager